GC Insights: Geoscience students' experience of writing academic poetry as an aid to their science education - A. Wardle; S. Illingworth (Geoscience Communication, 2022)
A survey was completed by 11 geoscience students in order to explore their experience of writing poetry as an aid to their science education. A thematic analysis found that themes could be categorised as being related to either the “Task Process” (“Identification of Significant Information”, “Distillation of Information”, “Metamorphosis of Text”) or “Task Meaning” (“Enjoyable”, “Valuable”, “Challenging”, which has sub-themes “Frustrating” and “Restricted”). The results of this study present evidence that writing haikus based on scientific texts can aid geoscience students by making newly learned information more digestible.